Mechanistic insights into the role of plant polyphenols and their nano-formulations in the management of depression - Kabra, Atul; Garg, Ruchika; Brimson, James; Živković, Jelena; Almawash, Saud; Ayaz, Muhammad; Nawaz, Asif; Hassan, Syed Shams Ul; Bungau, Simona (Frontiers in Pharmacology, 2022)
Depression is a condition characterized by low mood and an aversion to activity, that causes behavioral problems, poor quality of life and limits daily life activities. It is considered as the fourth leading cause of disability worldwide. Selective Serotonin Reuptake Inhibitors (SSRIs) Monoamine Oxidase (MAO) inhibitors, Tricyclic Antidepressants (TCAs), and atypical antidepressants are some of the conventional medications used to treat depression. However, only about half of patients with major depressive disorder (MDD) respond effectively to first-line antidepressant therapy. Additionally, there are a number of drawbacks to standard antidepressants, such as anti-cholinergic side effects, drug-drug interactions, and food-drug interactions, which prompts researchers to look at alternative approaches to the treatment of depression. Medicinal plants and their metabolites are extensively tested for their efficacy against depression. Electronic databases such as Google scholar, Science Direct, SciFinder and PubMed were used to search relevant literature on the role of polyphenols in depression. Plants-derived Polyphenols represent a major class of compounds extensively distributed in plants. Number of polyphenols have demonstrated antidepressant activity, among which berberine, piperine, curcumin, naringenin, ascorbic acid and ginsenosides are extensively evaluated. The medicinal plants and their derived compounds mediated synthesized green nanoparticles have also exhibited considerable efficacy in the management of depression. The therapeutic effects of these phytochemicals is mediated via differentiation and inhibition of neuronal cell apoptosis, promotion of neuronal cell survival and modulation of key neurotransmitters. The aim of this study is to review compressively the chemical, pharmacological and neurological evidence showing the potential of polyphenols in depression.